The missionary position Mother Teresa in theory and practice - Hitchens, Christopher (New York Twelve, 2012)
A religious fundamentalist, a political operative, a primitive sermonizer, and an accomplice of worldly secular powers. Her mission has always been of this kind. The irony is that she has never been able to induce anybody to believe her. It is past time that she was duly honored and taken at her word."
Keywords: Teresa, Mother, Saint, 1910-1997.